2014
DOI: 10.1016/j.cell.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Eukaryotic Cell-Cell Fusion

Abstract: Cell-cell fusion proteins are essential in development. Here we show that the C. elegans cell-cell fusion protein EFF-1 is structurally homologous to viral class II fusion proteins. The 2.6 Å crystal structure of the EFF-1 trimer displays the same 3D fold and quaternary conformation of postfusion class II viral fusion proteins, although it lacks a nonpolar "fusion loop," indicating that it does not insert into the target membrane. EFF-1 was previously shown to be required in both cells for fusion, and we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 56 publications
5
156
0
Order By: Relevance
“…Given the absence of any apparent genetic homology between organisms using this fold for membrane fusion, it is conceivable that the class-II fusion scaffold has evolved considerably from a common viral ancestor, as has been suggested for the lineage of viruses harboring upright β-barrel capsid proteins (46). As revealed by the crystal structure of the Caenorhabditis elegans EFF-1 fusion protein (20), it is also possible that the class-II fold is of cellular origin and viruses have coopted it, adding functionality to the scaffold [e.g., the addition of hydrophobic fusion peptide(s)] in the process. Irrespective, the conservation of this fold is reflective of the absolute necessity for genetically and pathobiologically diverse viruses to preserve a fundamental function throughout a long evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the absence of any apparent genetic homology between organisms using this fold for membrane fusion, it is conceivable that the class-II fusion scaffold has evolved considerably from a common viral ancestor, as has been suggested for the lineage of viruses harboring upright β-barrel capsid proteins (46). As revealed by the crystal structure of the Caenorhabditis elegans EFF-1 fusion protein (20), it is also possible that the class-II fold is of cellular origin and viruses have coopted it, adding functionality to the scaffold [e.g., the addition of hydrophobic fusion peptide(s)] in the process. Irrespective, the conservation of this fold is reflective of the absolute necessity for genetically and pathobiologically diverse viruses to preserve a fundamental function throughout a long evolutionary history.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies of the cognate Gc from RVFV (17) in the prefusion conformation revealed that the phleboviral Gc forms a class II architecture, which has been also observed for envelope glycoproteins from positive-sense RNA viruses from the Togaviridae and Flaviridae families (18,19). A similar class II architecture has also been observed in cell-cell fusion proteins, although the mechanism of membrane fusion is likely to differ from viral fusion as evident by the absence of a hydrophobic fusion loop (20).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Bearing semblance to the different classes of viral fusion proteins, cellular fusogens have been classified into class I and II: class I containing large alpha-helical domains, and class II defined by beta-sheet structures. The class II cellular fusogens share a common ancestral gene [119], later in evolution hijacked by different viruses [120]. Class I viral fusogens derive from retroviral genes [8].…”
Section: Towards An Understanding Of Viral and Cellular Fusionmentioning
confidence: 99%
“…It is involved in a large range of biological process such as mating, fertilization, muscle, bone and placenta organogenesis, immune response, tumorigenesis, and cell-mediated tissue regeneration (review in [1][2][3][4][5]). While cell fusion remains a relatively rare event restricted to particular cell types in animals, it constitutes a defining feature of the lifestyle of most filamentous fungi and slime moulds.…”
Section: Introductionmentioning
confidence: 99%